2004
DOI: 10.1074/jbc.m406071200
|View full text |Cite
|
Sign up to set email alerts
|

Differential Sensitivity of Phosphatidylinositol 3-Kinase p110γ to Isoforms of G Protein βγ Dimers

Abstract: The ability of G protein ␣ and ␤␥ subunits to activate the p110␥ isoform of phosphatidylinositol 3-kinase (PtdIns 3-kinase) was examined using pure, recombinant G proteins and the p101/p110␥ form of PtdIns 3-kinase reconstituted into synthetic lipid vesicles. GTPactivated G s , G i , G q , or G o ␣ subunits were unable to activate PtdIns 3-kinase. Dimers containing G␤ 1-4 complexed with ␥ 2 -stimulated PtdIns 3-kinase activity about 26-fold with EC 50 values ranging from 4 to 7 nM. G␤ 5 ␥ 2 was not able to sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
61
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(69 citation statements)
references
References 87 publications
(154 reference statements)
8
61
0
Order By: Relevance
“…For example, by substituting the charged amino acid within residues 44 -54 of G␤ with alanines, we confirmed the results from the peptide-based studies that these residues play a critical role in PLC␤2 activation (Chen et al, 2005). Although we have not yet evaluated the contribution of different amino acids of G␤ to PI3K activation, previous studies from Garrison's group demonstrated that mutation of residues H311, R314, and V315 impaired the ability of G␤␥ to activate PI3K␥ (Kerchner et al, 2004). These residues are contained in the peptide 309 -316, which inhibited ϳ20% of G␤␥-dependent PI3K activity in our studies.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…For example, by substituting the charged amino acid within residues 44 -54 of G␤ with alanines, we confirmed the results from the peptide-based studies that these residues play a critical role in PLC␤2 activation (Chen et al, 2005). Although we have not yet evaluated the contribution of different amino acids of G␤ to PI3K activation, previous studies from Garrison's group demonstrated that mutation of residues H311, R314, and V315 impaired the ability of G␤␥ to activate PI3K␥ (Kerchner et al, 2004). These residues are contained in the peptide 309 -316, which inhibited ϳ20% of G␤␥-dependent PI3K activity in our studies.…”
Section: Discussionsupporting
confidence: 86%
“…However, an almost perfect fit between the simulations and empirical data for both GRK2-ct and RACK1 can be achieved when either the affinities of G␤1␥2 for RACK1 and GRK2-ct are set to be twofold lower (200 and 1040 nM, respectively), or the affinity of G␤1␥2 for PI3K␥ is set to be twofold higher (2.8 nM; Supplementary Figure S2, B and C). Because these values are well within the range of variations reported for each parameter in the literature (Pumiglia et al, 1995;Maier et al, 1999;Maier et al, 2000;Kerchner et al, 2004;Chen et al, 2005), this indicates that the experimental data we obtained for both GRK2-ct and RACK1 are comparable to the theoretical predictions. Taken together, these results indicate that like GRK2-ct, RACK1 regulates PI3K␥ activity by competitive binding to G␤␥.…”
Section: Rack1 Inhibits G␤␥-induced Pi3k␥ Activation By Steric Hindrancesupporting
confidence: 87%
See 2 more Smart Citations
“…Activation of Erk also affects insulin secretion and proliferation of β-cells (Sonoda et al, 2008). Activation of the phosphatidylinositol 3 kinase (PI3K) pathway by GLP-1 has also been reported either through direct activation by the β/γ-subunits of Gs (Kerchner et al, 2004) or through an indirect pathway involving c-src-mediated transactivation of the epidermal growth factor receptor (EGFR) (Buteau et al, 2003).…”
Section: Introductionmentioning
confidence: 99%